Ukraińskie przygotowania wojskowe do „wyprawy kijowskiej” - Legieć, Jacek (Acta Universitatis Lodziensis. Folia Historica, 2001)
On the turn of 1919/1920 the Polish-Ukrainian negotiations began. They led to the completion of bilateral allians in April 1920. Its consequence was the common military action in Ukraine. During the preparations to that action the Ukrainian side started to organize troops consisted of the Ukrainian prisoner of war and interned persons, the stayed on territory controled by the Polish army. The above article tries to reconstruct the process of troops formation and to show conditions, that decided about the actions’ efectiveness. The Ukrainians succeded to complete two staff managed infantry divisions with the Polish assistance. The 6th infantry division under command of collonel Marek Bezruczko and the VIth reserve brigade were formed in Brest on Bug. And the 2nd infantry division under command of collonel Ołeksander Udowyczenko and the IInd reserve brigade were formed in the region of Kamieniec Podolski. All the units consisted together of 5000 soldiers. Lack of people disturbed the further extension of troops. The was the reason why the tropps could not play any significant role during the military action in Ukraine. However both organized in Poland divisions were well trained, armed and equipted. They distingushed themselves among the other troops of Ukrainian Peoples Republic during all the campaign in 1920.